Dionysos : the new god - O'Connor, George (O'Connor, George. Olympians, 2022)
His story is told by the first Olympian herself, Hestia, Goddess of the hearth and home. From her seat in the center of Mt. Olympus, the first Olympian, Hestia, relates the rise of Dionysos, from his birth to a mortal mother, to his discovery of wine, his battles with madness and his conquering of death itself, culminating, finally, in his ascent to Olympus and Godhood -- the first new god and the last of the Pantheon.